Impact of Transformational Leadership on Employee Readiness to Industry 5.0 : A Double-Mediation Model - Hoblos, Jihad; Kumar, Amit; Davidson, Ross (Prabandhan: Indian Journal of Management, 2025)
Purpose : Transformational leadership is widely recognized for its positive influence on employee outcomes, including readiness for change. However, little is known about the specific mechanisms by which perceived organizational support (POS) and employee cognitive engagement (ECE) function in the context of Industry 5.0. Methodology : The theoretical foundation was based on the dynamic capability perspective and social cognitive theory. The data were collected via a structured online survey shared with employees from various organizations based in the UAE. IBM SPSS was used to conduct simple regression analysis, while AMOS was used to perform SEM. Findings : The findings revealed that transformational leadership had a significant positive influence on employee readiness for Industry 5.0, with the double mediation roles of POS and ECE in the relationship. Practical Implications : The study provided insights for leaders, organizational practitioners, and policymakers, highlighting the importance of engagement and supportive environments and engaging employees cognitively to navigate the complexities of this transformative era. Originality/Value : This article is the first to offer empirical insights into a set of relationships among transformational leadership, employee readiness, POS, and ECE. Moreover, this study contributed to the literature on organizational behavior, leadership studies, and change management by proposing a conceptual framework that explained readiness for change in the context of Industry 5.0.